MANAJEMEN KETELADANAN GURU RA BERPRESTASI DI YOGYAKARTA - Fu’ad Arif Noor (QURROTI, 2019)
This article aims to reveal the exemplary management of RA teachers with the highest achievement in Yogyakarta, so that RA teachers are able to become role models who do earnestly learn their lessons, by always seeking information to keep the lessons out of date (never up to date ), eager to teach, pay attention to students, be fair, have a bright expression, always look good, attractive and fun, responsive and alert, have great attention and extensive experience, and are able to motivate students to learn spirit. These qualities will lead teachers to become figures that are liked and admired by their students. And this will make it easier for teachers to do their job, namely teaching the material or material to students, eventually students are able to understand the matter conveyed to him. The focus of the attention of students on the personal teacher, is necessary in the success of the learning process and teaching. For students who are interested in their teacher, they will be obedient to the teacher. And he will do whatever he is told. Indirectly, they will imitate something that is inside the teacher's person. Allah SWT reminds: "Very much hatred in the sight of Allah that you say anything that you do not do" (QS. As-Shoff, 61: 3).